Urinary 8-hydroxy-2′-deoxyguanosine levels and small-for-gestational age infants: a prospective cohort study from the Japan Environment and Children’s Study - Mitsuaki Hosoya; Koichi Hashimoto; Seiji Yasumura; Tsuyoshi Murata; Hyo Kyozuka; Toma Fukuda; Yuta Endo; Aya Kanno; Shun Yasuda; Akiko Yamaguchi; Akiko Sato; Yuka Ogata; et al. (BMJ Open)
Objectives To evaluate the association between the urinary 8-hydroxy-2′-deoxyguanosine (U8-OHdG) levels and the incidence of small-for-gestational age (SGA) infants and to assess the utility of U8-OHdG as a biomarker to predict the incidence of SGA infants.Design Prospective cohort study.Setting The Japan Environment and Children’s Study.Participants Data of participants enrolled in the Japan Environment and Children’s Study, a nationwide birth cohort study, between 2011 and 2014 were analysed; 104 062 fetal records were analysed. Data of women with singleton pregnancies ≥22 weeks of gestation were analysed.Primary and secondary outcome measures U8-OHdG levels were assessed using liquid chromatography-tandem mass spectrometry. Participants were categorised into the following three groups according to the quartile of the distribution of U8-OHdG: low U8-OHdG (<1.95 ng/mgCre), moderate U8-OHdG (the combined second and third quartiles; 1.95–2.95 ng/mgCre) and high U8-OHdG (>2.95 ng/mgCre) groups. Additionally, participants in the 90th percentile for U8-OHdG levels were analysed. Odds ratios (ORs) for SGA infants (<−1.5 and <−2.0 SD) were calculated using a logistic regression model while adjusting for confounding factors; the moderate U8-OHdG group was used as a reference. The cut-off value of U8-OHdG to predict the incidence of SGA infants was calculated using a receiver operating characteristic (ROC) curve analysis.Results Data of 80 212 participants were analysed. The adjusted ORs for SGA infants (<−1.5 and<−2.0 SD) in the high U8-OHdG group were 1.16 (95% CI 1.07 to 1.25) and 1.22 (95% CI 1.07 to 1.38). The cut-off value of U8-OHdG (3.26 ng/mgCre) showed a poor ability to predict SGA infants (sensitivity, 21.9%; specificity, 83.6%; area under the ROC curve, 0.530).Conclusions Elevated U8-OHdG levels were associated with an increased incidence of SGA infants. However, this parameter would not be a useful screening tool for predicting SGA infants owing to its low sensitivity and specificity.